Beautiful life - Portes, Gil M. (Regal Entertainment, 2004)
Beautiful life is a timely drama about the heartbreaking, impact of a terrorist act on eight women whose loved ones are killed at an airport bombing. Playing the grieving mothers, wives, daughters, and girlfriends who must deal with an imaginable loss.